Systematic review and meta-analysis of the prognostic impact of cancer among patients with acute coronary syndrome and/or percutaneous coronary intervention - Roule, Vincent (BMC Cardiovasc Disord, 2020)
BACKGROUND: Patients with cancer admitted for an acute coronary syndrome (ACS) and/or percutaneous coronary intervention (PCI) represent a growing and high-risk population. The influence of co-existing cancer on mortality remains unclear in such patients. We aimed to assess the impact of cancer on early and late, all-cause and cardiac mortality in the setting of ACS and/or PCI. METHODS: We performed a systematic review and meta-analysis of studies comparing outcomes of patients with and without a history of cancer admitted for ACS and/or PCI. RESULTS: Six studies including 294,528 ACS patients and three studies including 39,973 PCI patients were selected for our meta-analysis. Patients with cancer had increased rates of in-hospital all-cause death (RR 1.74 [1.22; 2.47]), cardiac death (RR 2.44 [1.73; 3.44]) and bleeding (RR 1.64 [1.35; 1.98]) as well as one-year all-cause death (RR 2.62 [1.2; 5.73]) and cardiac death (RR 1.89 [1.25; 2.86]) in ACS studies. Rates of long term all-cause (RR 1.96 [1.52; 2.53]) but not cardiac death were higher in cancer patients admitted for PCI. CONCLUSION: Cancer patients represent a high-risk population both in the acute phase and at long-term after an ACS or PCI. The magnitude of the risk of mortality should however be tempered by the heterogeneity among studies. Early and long term optimal management of such patients should be promoted in clinical practice.